2005
DOI: 10.1016/j.jmhg.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regular physical exercise on serum leptin and androgen concentrations in young women

Abstract: Background: The effects of short-term and long-term regular exercise on body mass index and early follicular phase serum levels of leptin, testosterone and dehydroepiandrosterone sulfate in young female subjects are presented in this study. Methods: Volunteer young women (n = 94) participated. The volunteers were divided into three groups. Group I, the control group had a sedentary lifestyle. Group II had exercised regularly for more than 10 hours a week for 5 years. Group III had exercised for over 10 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…We and other have reported a positive correlation between BMI and circulating peripheral leptin concentration in nonpregnant (36), and pregnant women (10)(11). In this study, it was found a mild positive correlation between maternal serum leptin concentration and BMI.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We and other have reported a positive correlation between BMI and circulating peripheral leptin concentration in nonpregnant (36), and pregnant women (10)(11). In this study, it was found a mild positive correlation between maternal serum leptin concentration and BMI.…”
Section: Discussionsupporting
confidence: 60%
“…The increase in serum leptin and ghrelin level was greater in the women with SPE than that of the MPE group. Parallel increased umbilical venous and arterial leptin and ghrelin concentrations may partly originate from the placenta (14,(28)(29)(30)(31)(32)(33)(34)(35)(36). Ghrelin, leptin and their mRNAs are present in rat (31) as well in human placenta (30).…”
Section: Discussionmentioning
confidence: 99%